Comparison of Economic Sector Performance and Its Impact on Poverty in Gorontalo Province and North Sulawesi Province - Ginndy Pratiwi Putri Damiti; Sri Indriyani S. Dai (Gorontalo State University, 2021)
This study aims to identify and analyze the performance of the economic sector on poverty in 2013-2017. The variables in this study are poverty as the dependent variable, and primary sector economic growth, secondary sector economic growth, and tertiary sector economic growth as independent variables. The data used in this study is secondary data obtained from BPS (Central Statistics Agency) Gorontalo Province and North Sulawesi Province. The analysis method used is panel data regression with a fixed effect model approach. In processing the data, the author uses the help of E-views 9 software. Based on the estimation results, it is found that the primary sector economic growth has a positive effect on poverty in Gorontalo Province. Meanwhile, the primary sector has a negative effect in North Sulawesi Province. Secondary sector economic growth has a negative effect on poverty in Gorontalo Province. Meanwhile, the secondary sector economic growth has a positive effect in North Sulawesi Province. Tertiary sector growth has a positive effect on poverty in Gorontalo Province. Meanwhile, the tertiary sector has a positive effect in North Sulawesi Province. Keywords: Poverty; Sectoral Economic Growth